The 2020 Hpakant Jade Mine Disaster, Myanmar: A multi-sensor investigation for slope failure - Lin, Yunung Nina; Park, Edward; Wang, Yu; Quek, Yu Pin; Lim, Jana; Alcantara, Enner [UNESP]; Loc, Ho Huu (Elsevier, 2021)
A quarry failure along the slopes of the Wai Khar open-pit jade mine in Hpakant, Myanmar has led to the deaths of at least 172 jade miners on 2 July 2020. This paper conducts a systematic investigation of the incident by integrating data from multiple sensors, including high-resolution optical imagery, Sentinel-1 synthetic aperture radar (SAR) images, unmanned aerial system (UAS) footage, SRTM and ALOS digital elevation models (DEMs), soil moisture product from multi-spectral Landsat-8 satellite and precipitation records from the Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS). Optical imagery, UAS footage and DEMs allow us to build a comprehensive mapping of tailing areas and quarry scarps from 2010 and reconstruct the 2D pit geometry prior to failure. Deformation signals from multi-temporal SAR interferometry (MTInSAR), soil moisture variations and precipitation trends further allow us to identify possible failure causes. To evaluate the quality of deformation obtained from different distributed-scatterer phase estimators, we develop an empirical mapping function based on areal fraction values to facilitate the comparison of temporal coherence values that are differently formulated in each phase estimator. The comparison shows that phase linking algorithm outperforms the small baseline subset method in terms of signal recovery and phase reliability. Our investigation points out that the mining site is under aggressive mining cycles that are exacerbated by frequent, uncontrolled landslides. Seepage failure, which involves the expulsion of water from rapidly compacting tailings, may be a critical factor in the 2020 incident. Instead of extreme weather, the failure had occurred under normal to drier conditions. This means that the sliding planes were already in a critical state, which is evident from the accelerated deformation around the collapse area since the beginning of 2020. Based on these findings, we provide recommendations to improve mining site regulations and management practices for safer open-pit mining in Myanmar and probably in similar contexts outside Myanmar.
Keywords: InSAR time-series; Jade mine in Myanmar; Open-pit mine; Phase linking; Seepage failure; Slope failure